Thinking about (hidden) criminalisation - Farmer, Lindsay (International Journal for Crime, Justice and Social Democracy, 2018)
Criminalisation is now seen as one of the central issues in criminal law theory. However, in spite of the (rather belated) recognition of the importance of the topic, a number of fundamental questions remain unaddressed (Duff et al. 2014) and, in many cases, not even openly acknowledged. I discuss three such questions here, prompted by the articles in this excellent special issue on ‘Hidden Criminalisation’ and, in doing so, I raise a fourth and broader issue about the possible limits of criminalisation theory